Complementary Feeding Practices and Associated Factors Among Nursing Mothers in Southwestern Nigeria - Folake Olukemi Samuel, MSc, PhD; Ebunoluwa Grace Ibidapo, MPH (Global Health and Education Projects, Inc., 2020)
Background and Objectives: The period of transition from breastfeeding to other foods and liquids, is a very vulnerable period when malnutrition is likely to start in many infants and young children, if appropriate feeding practices are not employed. This study assessed using composite indices, the appropriateness of complementary feeding practices and associated factors among nursing mothers in Ijebu-Ode, Ogun State. Methods: This descriptive cross sectional study was conducted in selected primary health facilities in Ijebu-Ode. Multi stage sampling technique was employed to select 283 mother-child pairs. Data was collected using a pre-tested interviewer administered questionnaire which included the World Health Organization Infant and Young Child Feeding Indicators (WHO IYCF) and the Infant and Child Feeding Index (ICFI). Results: Of the total 283 mother-child pairs studied, 33.6% met minimum meal frequency, 14.5% received minimum dietary diversity (?4 food groups) and 9.2% received minimum acceptable diet when assessed using the WHO IYCF indicators. Overall, appropriate complementary feeding was low (4.2%) and associated (p?0.05) with factors such as antenatal care visits, child welfare clinic attendance and mother's workplace. On the other hand, the ICFI categorized respondents into low (11.7%), medium (24.7%) and high (63.6%) ICFI scores and were associated (p?0.05) with mother's education and household size. Conclusion and Global Health Implications: This study revealed a high prevalence of inappropriate complementary feeding practices. The use of composite indices reflected these practices and their associated factors holistically as they revealed different dimensions of complementary feeding. This may be useful for monitoring, evaluation, research and the required advocacy for complementary feeding. Key words: • Appropriate complementary feeding • IYCF indicators • Feeding practices • Infant and child feeding index   Copyright © 2020 Samuel and Ibidapo. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.